2019
DOI: 10.1039/c9cp01814j
|View full text |Cite
|
Sign up to set email alerts
|

Computational characterisation of structure and metallicity in small neutral and singly-charged cadmium clusters

Abstract: Putative global minimum structures for neutral Cd N and singly charged Cd + N and Cd − N clusters in the small size regime up to N = 21 atoms are reported. A global optimization approach based on the basin hopping method and a Gupta potential fitted to cluster properties is employed to generate a diverse databank of trial structures, which are then re-optimized at the densityfunctional level of theory. Novel, previously unreported, structures are found for many sizes. Our results successfully reproduce and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…All these structures exhibit a trigonal bipyramidal Cd 5 unit as main building block. Previously, lowest‐energy structures of Cd x + clusters were reported 27 . In our GO procedure we have found all the proposed Cd x + structures and additionally new ones with lower energy for x = 4, 5, 7, 8.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…All these structures exhibit a trigonal bipyramidal Cd 5 unit as main building block. Previously, lowest‐energy structures of Cd x + clusters were reported 27 . In our GO procedure we have found all the proposed Cd x + structures and additionally new ones with lower energy for x = 4, 5, 7, 8.…”
Section: Resultsmentioning
confidence: 60%
“…In our GO procedure we have found all the proposed Cd x + structures and additionally new ones with lower energy for x = 4, 5, 7, 8. The energetic stabilization of the new lowest energy structures are given in eV in brackets relative to the ones recently proposed: 27 Cd 4 + (0.14), Cd 5 + (0.17), Cd 7 + (0.14) and Cd 8 + (0.02). On the other hand, pure Se y + clusters for y = 3 already possess an angled geometry and larger species form ring structures as it is known for neutral Se clusters in which all selenium atoms are twofold coordinated 28,29 .…”
Section: Resultsmentioning
confidence: 99%
“…Zhao calculated that Cd n clusters that have closed electronic shells demonstrate magic number behavior for some n , and the size dependence of ionization potentials converges towards the bulk limit. 17 While Alvarez et al showed that metallicity of Cd n clusters emerges as a result of sp-hybridization, 18 and a study by Kohaut et al revealed that such clusters do not show metallic properties up to n = 60. 19 Besides, Oyeniyi et al developed and used a method to calculate the electronic excitation energies and absorption spectra of zero dimensional Zn, Cd and S clusters.…”
Section: Introductionmentioning
confidence: 99%